In vitro assessment of safety and probiotic potential characteristics of Lactobacillus strains isolated from water buffalo mozzarella cheese - Casarotti, Sabrina Neves [UNESP]; Carneiro, Bruno Moreira; Todorov, Svetoslav Dimitrov; Nero, Luis Augusto; Rahal, Paula [UNESP]; Penna, Ana Lúcia Barretto [UNESP] (Springer Nature, 2017)
The aim of this study was to evaluate the safety and probiotic potential characteristics of ten Lactobacillus spp. strains (Lactobacillus fermentum SJRP30, Lactobacillus casei SJRP37, SJRP66, SJRP141, SJRP145, SJRP146, and SJRP169, and Lactobacillus delbrueckii subsp. bulgaricus SJRP50, SJRP76, and SJRP149) that had previously been isolated from water buffalo mozzarella cheese. The safety of the strains was analyzed based on mucin degradation, hemolytic activity, resistance to antibiotics and the presence of genes encoding virulence factors. The in vitro tests concerning probiotic potential included survival under simulated gastrointestinal (GI) tract conditions, intestinal epithelial cell adhesion, the presence of genes encoding adhesion, aggregation and colonization factors, antimicrobial activity, and the production of the β-galactosidase enzyme. Although all strains presented resistance to several antibiotics, the resistance was limited to antibiotics to which the strains had intrinsic resistance. Furthermore, the strains presented a limited spread of genes encoding virulence factors and resistance to antibiotics, and none of the strains presented hemolytic or mucin degradation activity. The L. delbrueckii subsp. bulgaricus strains showed the lowest survival rate after exposure to simulated GI tract conditions, whereas all of the L. casei and L. fermentum strains showed good survivability. None of the tested lactobacilli strains presented bile salt hydrolase (BSH) activity, and only L. casei SJRP145 did not produce the β-galactosidase enzyme. The strains showed varied levels of adhesion to Caco-2 cells. None of the cell-free supernatants inhibited the growth of pathogenic target microorganisms. Overall, L. fermentum SJRP30 and L. casei SJRP145 and SJRP146 were revealed to be safe and to possess similar or superior probiotic characteristics compared to the reference strain L. rhamnosus GG (ATCC 53103).
Keywords: Antibiotic resistance; Beneficial properties; Dairy; Gastrointestinal tract survival; Lactic acid bacteria; Safety